2001
DOI: 10.1029/2000jc000371
|View full text |Cite
|
Sign up to set email alerts
|

Modes and mechanisms of ocean color variability in the Santa Barbara Channel

Abstract: Abstract. Characterizing the substances, processes, and mechanisms that regulate ocean color variability is crucial for assessing marine resources and impacts of land-ocean interactions with remote sensing data. Bimonthly optical and in situ water column observations from a 3-year field program within the Santa Barbara Channel, California, are used to assess sources of ocean color variability in a semiarid coastal region. Correlation analyses demonstrate that remote sensing reflectance variability is tightly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 37 publications
14
57
0
Order By: Relevance
“…7, being excluded), with a rather seasonally stable mixed-layer depth (20-50 m) and average [Chl] of around 2 mg m 23 , with higher chlorophyll levels from April to July and lower values in the fall. Intense blooms are found within the SBC, usually in late spring (Toole and Siegel 2001;Otero and Siegel 2004). However, the timing of the spring blooms varies enough from year to year to smear out the mean annual cycle signal (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7, being excluded), with a rather seasonally stable mixed-layer depth (20-50 m) and average [Chl] of around 2 mg m 23 , with higher chlorophyll levels from April to July and lower values in the fall. Intense blooms are found within the SBC, usually in late spring (Toole and Siegel 2001;Otero and Siegel 2004). However, the timing of the spring blooms varies enough from year to year to smear out the mean annual cycle signal (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1B). The SBC is an optically complex coastal site in which optical properties are affected by phytoplankton blooms, sediment plumes, and other episodic events, including mixing of various water masses (Toole and Siegel 2001;Otero and Siegel 2004;Kostadinov et al 2007). There is a complex mix of cold water of relatively low salinity upwelled off Point Conception and warm, saltier Southern California Bight waters (Harms and Winant 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this backscattering resulting in high values of upwelling radiation in the green-yellow band (λ = 555 nm) was used. The nLw555 product is commonly utilized to distinguish river plumes, and was strongly correlated with TSS concentration ([TSS]) in near-surface waters (Lahet et al, 2001;Loisel et al, 2001;Toole & Siegel, 2001;Otero & Siegel, 2004;Nezlin & Di Giacomo, 2005;Thomas & Weatherbee, 2006). For each scene, the plume extension was delimited by thresholding of the nLw555 image.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…The spectra were relatively not sensitive to changes in the concentrations of Chl a and CDOM under high concentrations of suspended sediments [34,35], but at lower concentrations of suspended sediments, the data may have been influenced by the concentrations of Chl a and CDOM based upon the absorption characteristics. Previous research used empirical orthogonal function (EOF) analysis to study similar turbid waters and the results indicated that 74% [10] or nearly two-thirds [44] of the total variance of R rs can be partly explained by particulate backscattering (b bp ), whereas particulate and dissolved absorption only explained 15% [10] or 30% [44] of the ocean color variability based on different data sets. The associated classification results were shown to be a good tool for an inversion algorithm in previous research too [10,45].…”
Section: Analysis For the Imagery Classification Resultsmentioning
confidence: 99%